Influence of Earthworm Activity on Soil Fertility in Agroforestry Systems - Saharan, Neelam; Singh, R P (Annals of Arid Zone, 2016)
Investigations were carried out to study the effect of earthworm activity Oft fertility status of rainfed red sandy loam soil under Acacia tortilis and Leucaena leucocephalo in association with Stylosanthes hamata and Cenchrus ciliaris. Earthworm casts were more abundant and of larger size around A. tortilis than around L. leucocephala. The pH and EC values increased due to earthworm activity whereas silt and clay contents decreased in the casts. Worm-casts contained 1.2 to 1.7 times more available P205 and 1.4 to 1.6 times more available K20 as compared to the parent soil collected from 15 cm depth. As a result of earthworm activity. 12 g of organic carbon. 39 mg of nitrogen, 19 mg of P20S and 192 mg of K20 were added per square metre area around A tortiUs by 64 worm-casts whereas 1.43 g organic carbon. 5.4 mg nitrogen,3.5 mg P205 and 17 mg K20 were increased per square metre around L.leucocephala t S. hamata by 54 worm-casts and 0.87 g organic carbon, 4.9 mg nitrogen, 2.6 mg P205 and 15 mg K20 were increased per square metrearound L. leucocephala + C. ciliaris by 44 worm-casts.